SUBOPTIMAL CONTROL OF SINGULARLY DRILLED WITH THE DISTRIBUTED SYSTEM - Mykhailova, T. F. (Science and Transport Progress, 2006)
The article proposes a method of approximated solution of a singular/excited task of optimal control of the intensive electrolysis process. The suboptimum control and the quality criterion, using asymptotics of the zero order, have been constructed and the closeness of obtained approximated solutions to the exact ones has been assessed.